Electromagnetic Flux Analysis of Ds Hesfm for Directly Driven Actuator Used in Aircraft Applications - Soomro, H. A.; Sulaiman, E.; Jenal, M.; Omar, M. F.; Jusoh, L. I.; Rahimi, S.K. (International Journal of Engineering and Technology, 2018)
This paper presents the electromagnetic flux analysis of dual stator hybrid excitation switched flux machines (DS HESFM) using segmental rotor for the directly driven electromechanical actuator aimed to use in aerospace applications. The advantage of designing a machine with directly driven system is to eliminate the intermediate gear box system with having minor component count and reduced jamming possibility. The proposed design of DS hybrid excitation with high torque density is investigated in this paper as a potential solution for aircraft applications.Â The key intentions of the design are high level of actuator integration to reduce the overall weight and volume and fault tolerance ability. The proposed design of DS HESFSM has simple structure, which consist of only six field excitation coils (FECs) housed in outer stator along with six armature coils (ACs) whereas, six permanent magnets (PMs) are positioned in the inner stator. Moreover, DS HESFM structure is analyzed at open circuit and short circuit conditions conditions by means of â€œcommercial 2D FEA package, JMAG-designer ver. 14.0,â€ released by JSOL Corporation.